1996
DOI: 10.1128/jb.178.11.3146-3155.1996
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that SbcB and RecF pathway functions contribute to RecBCD-dependent transductional recombination

Abstract: A role for the RecF, RecJ, and SbcB proteins in the RecBCD-dependent recombination pathway is suggested on the basis of the effect of null recF, recJ, and sbcB mutations in Salmonella typhimurium on a "short-homology" P22 transduction assay. The assay requires recombination within short (ϳ3-kb) sequences that flank the selected marker and lie at the ends of the transduced fragment. Since these ends are subject to exonucleolytic degradation, the assay may demand rapid recombination by requiring that the exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 66 publications
0
31
0
Order By: Relevance
“…1 are not necessarily as distinct as shown. For example, some evidence exists that the RecF pathway functions may participate in RecBCDmediated recombination pathways under at least some conditions (Miesel & Roth 1996). Second, the resolution of the recombination crossover in either pathway can occur in two ways.…”
Section: Quantifying Step 1 Under Normal Growth Conditionsmentioning
confidence: 99%
“…1 are not necessarily as distinct as shown. For example, some evidence exists that the RecF pathway functions may participate in RecBCDmediated recombination pathways under at least some conditions (Miesel & Roth 1996). Second, the resolution of the recombination crossover in either pathway can occur in two ways.…”
Section: Quantifying Step 1 Under Normal Growth Conditionsmentioning
confidence: 99%
“…First, defects in recombination are seen when two or three are defective (30,35,46). Second, we show here that lack of even two can be mutagenic via increased SOS induction and PolIV up-regulation.…”
Section: Sos Induction In Most Exoimentioning
confidence: 99%
“…Single-strand-specific exonucleases of either 5Ј or 3Ј polarity are required for normal levels of homologous recombination (30,35,46) and presumably recombinational repair. In their absence, recombination of linear substrates is reduced (30,35,46), suggesting that processing of double-strand ends to yield either 3Ј or 5Ј singlestrand overhangs promotes recombination (35,37,40).In the E. coli methyl-directed mismatch repair system, single-strand-specific exonucleases are required for degradation of the nicked, error-containing strand in vitro (44). The polarity of the exonuclease required depends on the location of the incision relative to the mismatch, and any of the four semiredundant single-strand-specific exonucleases is sufficient (44).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests that either exonuclease V or IX is required for systemic infection and hence that RecJ can participate in RecBCD-mediated recombinational repair in the absence of the RecD subunit. Previous observations have suggested that RecD and RecJ provide alternative functions for recombinational repair of DNA damage in both Salmonella (11,23,27) and E. coli (39). Function redundancy may thus explain why RecD Ϫ and RecJ Ϫ single mutants are virulent (Table 2; see also reference 40).…”
mentioning
confidence: 99%